Bridging Aspirations and Policy: An Analysis of Community Input Absorption from Recess Activities of the Regional People's Representative Council in Bengkulu Province - Dani, Rahiman; Purnawan, Heru (Universitas Teuku Umar, 2025)
This study analyzes the effectiveness of recess activities conducted by members of the Regional People's Representative Council of Bengkulu Province in fostering local democracy and promoting community economic development. The research aims to assess how well community aspirations gathered during recess are translated into actionable programs within the 2018 Revised Regional Government Budget. Employing survey methods and literature review, the study classifies and quantifies the absorption of